An account of the proceedings in the University of Cambridge, against William Frend, M.A. Fellow of Jesus College, Cambridge, for publishing a pamphlet, intitled peace and union, &c. containing the proceedings in Jesus college, the trial in the vice-chanceller's court, and in the court of delegates. Publ. by the defendant (Flower, 1793)
With index.